Phase III trial of 8% vaginal progesterone gel for luteal phase support in Japanese women undergoing in vitro fertilization and fresh embryo transfer cycles. (1st December 2016) - Kokeguchi, Shoji; Hayashi, Naoki; Rogoff, Daniela; Shimizu, Shin; Ishihara, Osamu
Abstract: Aim: This study evaluated the efficacy and safety of vaginal progesterone gel that was administered daily for luteal phase support as part of in vitro fertilization/embryo transfer (IVF/ET) cycles in Japanese women. Methods: This was a phase III, multicenter, open‐label, single‐arm trial in Japanese women undergoing IVF/ET, using the Japanese Society of Obstetrics and Gynecology 2009 registry as a historical control. The primary objective was to demonstrate the non‐inferiority, with regard to the clinical pregnancy rate per ET, of vaginal progesterone gel that was administered once daily, compared with the historical standard value in IVF/ET cycles in Japan. The biochemical pregnancy (positive serum β‐hCG pregnancy test but no clinical pregnancy) rate per ET also was investigated, as were the safety and tolerability of the vaginal progesterone gel. Results: Of the 178 women who were enrolled, 123 underwent IVF/ET. The clinical pregnancy rate per ET was non‐inferior in the prospective arm, compared with the historical population. The biochemical pregnancy rate per ET was 7.3%. The safety profile of the vaginal progesterone gel was as expected, with no new safety issue identified. Conclusion: The vaginal progesterone gel was efficacious, with a safety profile as expected, in this study in Japanese women undergoing IVF/ET cycles.